Comparison of Dubowitz scoring versus Ballard scoring for assessment of fetal maturation of newly born infants setting - Singhal, Sangeeta; Bawa, Ritu; Bansal, Shivani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Different scoring systems based on neurological and physical examination are used in the neonatal units for assessment of gestational age. Assessment of gestational age is very much helpful in labelling the newborn to be preterm, term or post – term and to assess the further outcome of the newborn infants. Present study was performed to test the accuracy and reliability of the Ballard scoring system as compared to Dubowitz scoring system on 250 newborn infants and their correlation with the gestational age as calculated from first day of mother’s last menstrual period. In infants of 38 weeks onwards correlation of gestational age was done with the extension of plantar creases over sole. Methods: Infants studied were selected from infants born in Muzaffarnagar Medical College and Hospital Muzaffarnagar and those infants admitted to the neonatal intensive care unit. First of all methods of eliciting different criteria were experienced by examining several newborn infants and then Dubowitz and Ballard scoring system were performed separately and gestational age assessed. crease was measured, using metallic scale from base of great toe after stretching the sole. Results: Gestational ages estimated by Ballard scoring system and Dubowitz system strongly correlated with the gestational ages computed from the date of mother’s last menstrual period. The coefficient of correlation calculated between Ballard and Dubowitz scoring system showed perfect positive correlation on the regression line. Association of gestational age with the length of sole crease was also very significant. Conclusions: The clinical test of maturation described by Ballard et al and which is evaluated in the present study, takes a balanced look at physical and neurological maturation and included those items found to be most useful regardless of the presence or absence of diseased state.